Development and validation of online micro credential educational framework and evaluation of fire safety essentials course among health science students - Baharudin, Rozita (2025)
Micro-credentials (MCs) are increasingly recognized as short, flexible, and competency-focused learning approaches, accelerated by the COVID-19 pandemic and the rise of artificial intelligence. They provide structured platforms suitable for graduates and professional development, including reskilling and upskilling. Despite their potential, MCs remain under-researched, with limited standardized frameworks guiding their development. This study aims to develop and validate an educational framework for micro-credentials and to evaluate its effectiveness as a training tool, using the Fire Safety Essentials MC as a case study. The study was conducted in three phases. Phase one involved a scoping review to identify key elements for MC development, which were analysed thematically to generate domains and items. An expert evaluation by ten educators and MC specialists and educationist confirmed the framework’s relevance and usability. Phase two developed the Fire Safety Essentials MC based on this framework. The third phase evaluated its effectiveness by comparing two groups of health science students: face-to-face (F2F) learning and online learning using the micro-credential and training experiences were measured using the Training Evaluation Inventory. The total sample included 92 participants (46 per group), and assessments measured knowledge, skills, and training experience. The framework consisted of eight domains and 66 items: (1) learning outcomes, (2) instructional design, (3) learning activities, (4) course maps, (5) assessment, (6) feedback (7) digital badge and (8) institutional factors. Findings indicated that MC learners achieved higher knowledge scores, whereas F2F learners performed better in skills assessments However, both groups rated the training experience and instructional design comparably, with no significant differences. This study supports the use of MCs as an alternative or complement to F2F learning for health sciences graduates and other professionals. The validated framework provides guidance for designing effective MCs, while the Fire Safety Essentials course demonstrates its practical application. The framework also had the potential to serve as a checklist for the quality assurance process of micro-credential.